ANALISIS PARTISIPASI MASYARAKAT PADA POTENSI PARIWISATA DODU MELALUI PROGRAM KKN-TEMATIK WIRADESA STIE BIMA - Puji Muniarty; Wulandari Wulandari; M Syukur Dwiriansyah (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Village development is an important theme in implementing activities as a form of implementing learning outcomes on campus. The implementation of thematic Community Service Program in developing villages aims to build critical awareness of the community in order to build a more participatory community (village) and be able to find creative ideas. Through this Wiradesa KKN-T activity, it is hoped that the community can develop the potential and economic leverage of the region. The purpose of the study was to analyze the significance of community participation in the work program carried out by KKN students in the Dodu sub-district, Bima City. Descriptive research with a quantitative approach with a sample of 96 respondents. The data analysis technique used validity and reliability tests, participation level criteria tests and t tests. In general, choosing Lasatu to be a tourist attraction that needs to be developed because there is no special attention from the community makes this tour not known to many people, therefore we might be able to make this Lasatu tourist attraction a popular tourist attraction later to improve the economy in the Dodu village. Community participation is measured through 4 indicators, namely: Community activity in the implementation of development, willingness to contribute in the form of thoughts, expertise and skills, willingness to contribute in the form of money, responsibility for the success of development. The significance results show that the level of community participation in the development of "La Satu" tourism potential is in the category above 66%, which means it is in the high category.